Pengaruh Kebijakan Penurunan Denda Keterlambatan dan Perubahan Jatuh Tempo Pembayaran PBB-P2 terhadap Kepatuhan Wajib Pajak - Akhmad Andi Nugroho; Muhammad Khozin (JCOMENT (Journal of Community Empowerment), 2026)
This research aims to examine the impact of policies reducing late payment penalties and changing the due date for Rural and Urban Land and Building Tax (PBB-P2) on taxpayer compliance in Sleman Regency in 2024. This policy is outlined in Sleman Regency Regulation Number 86 of 2023, which stipulates a reduction in late payment penalty rates from 2% to 1% per month and extends the payment deadline to six months from the date the Tax Due Notice (SPPT) is issued. This study uses a quantitative approach with a causal survey method to analyze the influence of two independent variables on the dependent variable, namely taxpayer compliance. Data was obtained by distributing questionnaires to PBB-P2 taxpayers, which were then analyzed using descriptive statistics and path analysis with the help of SmartPLS software. The results of the study show that a reduction in late payment penalties and a change in payment due dates have a positive and significant influence on taxpayer compliance. The main factors influencing compliance are the desire to avoid sanctions, followed by adherence to government regulations. This finding aligns with Stimulus-Response theory and the Theory of Planned Behavior, which emphasize the role of motivation and social support in increasing tax compliance. Therefore, the Sleman Regency Government is advised to continue strengthening public socialization and education activities to ensure the effectiveness of tax policies.